2015
DOI: 10.1155/2015/910348
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Homogeneous Charge Compression Ignition and Low Temperature Combustion by Optical Diagnostics

Abstract: Optical diagnostics is an effective method to understand the physical and chemical reaction processes in homogeneous charge compression ignition (HCCI) and low temperature combustion (LTC) modes. Based on optical diagnostics, the true process on mixing, combustion, and emissions can be seen directly. In this paper, the mixing process by port-injection and direct-injection are reviewed firstly. Then, the combustion chemical reaction mechanism is reviewed based on chemiluminescence, natural-luminosity, and laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 104 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…The in-cylinder flow structure is also critical for PPC because of its influence on the fuel-air mixing process [21]. These patterns of incylinder gas movement can be studied by means of optically accessible engines [22] [23]. An outstanding technique to conduct this kind of research is particle image velocimetry (PIV) [24].…”
Section: Introductionmentioning
confidence: 99%
“…The in-cylinder flow structure is also critical for PPC because of its influence on the fuel-air mixing process [21]. These patterns of incylinder gas movement can be studied by means of optically accessible engines [22] [23]. An outstanding technique to conduct this kind of research is particle image velocimetry (PIV) [24].…”
Section: Introductionmentioning
confidence: 99%
“…This process reduces high flame fronts and maintains the in-cylinder temperatures at lower levels. In a study of HCCI and low temperature combustion with the aid of optics [40], it was demonstrated that near-zero NOx emissions were feasible due to low combustion temperature and high EGR attenuation. The overall homogenous lean air-fuel mixture also tends in avoiding the soot formation in emissions.…”
Section: Ltc Is Achieved Through a Variety Of Methods Such As Homogenmentioning
confidence: 99%